A 598-bp InDel Variation in the Promoter Region of Bna.SOC1.A05 Is Predominantly Present in Winter Type Rapeseeds - Matar, Sarah; Melzer, Siegbert (Frontiers in Plant Science, 2021)
During rapeseed domestication and breeding, genetic diversity allowed to adapt it to different eco-geographical regions and to shape its useful traits. Structural variations (SVs), including presence/absence variations (PAVs), are thought to play a major role in the genetic diversity and phenotypic plasticity of rapeseed. In this study, we detected a 598-bp PAV within the promoter region of an Arabidopsis ortholog of a major flowering time gene and a downstream target of FLC, SOC1, which is one of the first genes that are upregulated in rapeseed during vernalization. Further analysis showed that the insertion is present predominantly in winter types while absent in spring types. The 589-bp sequence is present only in the A sub-genome indicating that it originated from Brassica rapa. Since the genomic region around Bna.SOC1.A05 showed a strong reduction in nucleotide diversity, the insertion might represent a larger selected sweep for rapeseed adaptation. Cis-element analysis showed that the insertion contains an ACGTG box, which is the strongest binding motif for the HY5 transcription factor in Arabidopsis. In addition, expression analyses showed that mRNA levels of Bna.SOC1.A05 were lower in accessions carrying the insertion compared to the ones that had no insertion.